Analysis of Farmers' Motivation in Conducting Kencur Plant Business in Boyolali Regency - Fita Milasari, Ela; Setiyani, Rahmawati; Sepfrian, Bimoseno (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
Based on BPS data (2023) Boyolali Regency is the center of kencur production in Central Java because it is the producer of kencur production with a total of 1,502,570 kg. The constraints of Boyolali Regency are that farmers experience price fluctuations and unstable yields every year. Given that Boyolali Regency is a center of kencur in Central Java, this problem must be resolved immediately to increase productivity, food security, and find out strategies to increase productivity and efficiency in kencur farming. The data used are primary data and secondary data. The data collection methods used were interviews with resource persons, discussions, documentation. This research was analyzed using descriptive analysis, Likert's scale, and interval formula.